The relationship between the museum and its workers - a case at the Museu Vivo do São Bento in Duque de Caxias - RJ (Cadernos de Sociomuseologia, 2025)
The focus is on the insurgent actions that enabled the creation of a social museum as a space for political struggle, social transformation, and emancipation, revealing how these workers, through activism, contribute to decolonizing museum practices. Through interviews, this work aims to closely examine these workers and the museum-worker relationship to understand, from a social museum perspective, the specificities of this relationship, its impact on the worker, both as a worker and as an individual, as well as its gaps. At the end, the article demonstrates the role that activism and affection occupy in the museum, in the individual and in the worker-museum relationship, and how the actions of these workers were essential to the creation and maintenance of this space as a space for political struggle.Keywords: museum worker; social museum; work; social museology.